2005
DOI: 10.7748/ns2005.02.19.23.33.c3805
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ decision-making in clinical practice

Abstract: The decisions nurses make are directly related to the clinical areas in which they work. However, it would be interesting to know if nurses showed particular aptitudes for different types and levels of decision-making and if this is related to other factors such as personality, education and experience in nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
(24 reference statements)
2
22
0
2
Order By: Relevance
“…Part of the study done by Hoffman, Donoghue, and Duffield () explored the associations between age and clinical decision‐making in Australia nurses and established that older subjects in their study had a weak but significantly higher scores in their clinical decision‐making ( r = .223, p < .05). This finding agrees with other studies reporting that experienced nurses make more effective clinical decisions than less experienced nurses (Bakalis & Watson, ; Pantazopoulos et al., ). Bjørk and Hamilton () investigated factors affecting types of clinical decision‐making and found that years of working experience ( r = .132, p < .05) and increase age ( r = .059, p < .05) are significantly associated with clinical decision‐making.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Part of the study done by Hoffman, Donoghue, and Duffield () explored the associations between age and clinical decision‐making in Australia nurses and established that older subjects in their study had a weak but significantly higher scores in their clinical decision‐making ( r = .223, p < .05). This finding agrees with other studies reporting that experienced nurses make more effective clinical decisions than less experienced nurses (Bakalis & Watson, ; Pantazopoulos et al., ). Bjørk and Hamilton () investigated factors affecting types of clinical decision‐making and found that years of working experience ( r = .132, p < .05) and increase age ( r = .059, p < .05) are significantly associated with clinical decision‐making.…”
Section: Discussionsupporting
confidence: 93%
“…Sometimes it was used interchangeably with the term “clinical judgement” to describe the same phenomena (Thompson & Dowding, ). Some researchers emphasised clinical decision‐making as the utmost crucial component in nursing (Bakalis, ; Bakalis, Bowman, & Porock, ; Dowding et al., ; Wang, Chien, & Twinn, ) because, according to Bakalis and Watson (), nurses are often the first professionals to observe a rapid deterioration in the patient's physical state. Therefore, critical thinking is an essential means for them to critically analyse clinical situations in order to make fast and right decisions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the regression analysis in this research, the age of the nurses was found to be positively related with independent, intuitive, and rational DMS. It was reported that there was a positively significant correlation in the literature between decision‐making frequency and age (Bakalis & Watson, ; Ludin, ). There are studies in the literature that indicate that age does not affect DMS or there is a negative relationship between them (Sladek, Bond, & Phillips, ; Thunholm, ; Verma et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Bakalis and Watson (2005) found that the length of clinical experience was significantly correlated to the frequency of decision‐making, although there was no difference based on educational level of nurses. However, they did not give the statistical basis for these statements.…”
Section: Introductionmentioning
confidence: 92%